Leveraging ddRADseq for Uncovering New Genome-Wide and Polymorphic SSR Markers in Japanese Plum (Prunus salicina Lindl.) - C. V. Acuña; N. C. Aguirre; C. V. Filippi; M. N. García; J. G. Rivas; P. V. Villalba; A. V. Gutiérrez; M. C. Martínez; T. Cerrillo; G. H. Valentini; G. Sánchez; H. E. Hopp; et al. (Plant Molecular Biology Reporter, 2025)

Review of Environmental Monitoring by Means of Radio Waves in the Polar Regions: From Atmosphere to Geospace - Lucilla Alfonsi; Nicolas Bergeot; Pierre J. Cilliers; Giorgiana De Franceschi; Lisa Baddeley; Emilia Correia; Domenico Di Mauro; Carl-Fredrik Enell; Mark Engebretson; Reza Ghoddousi-Fard; Ingemar Häggström; Young-bae Ham; et al. (Surveys in Geophysics, 2022)
The Antarctic and Arctic regions are Earth's open windows to outer space. They provide unique opportunities for investigating the troposphere–thermosphere–ionosphere–plasmasphere system at high latitudes, which is not as well understood as the mid- and low-latitude regions mainly due to the paucity of experimental observations. In addition, different neutral and ionised atmospheric layers at high latitudes are much more variable compared to lower latitudes, and their variability is due to mechanisms not yet fully understood. Fortunately, in this new millennium the observing infrastructure in Antarctica and the Arctic has been growing, thus providing scientists with new opportunities to advance our knowledge on the polar atmosphere and geospace. This review shows that it is of paramount importance to perform integrated, multi-disciplinary research, making use of long-term multi-instrument observations combined with ad hoc measurement campaigns to improve our capability of investigating atmospheric dynamics in the polar regions from the troposphere up to the plasmasphere, as well as the coupling between atmospheric layers. Starting from the state of the art of understanding the polar atmosphere, our survey outlines the roadmap for enhancing scientific investigation of its physical mechanisms and dynamics through the full exploitation of the available infrastructures for radio-based environmental monitoring.

The γ-Protocadherins Interact Physically and Functionally with Neuroligin-2 to Negatively Regulate Inhibitory Synapse Density and Are Required for Normal Social Interaction - David M. Steffen; Sarah L. Ferri; Charles G. Marcucci; Kelsey L. Blocklinger; Michael J. Molumby; Ted Abel; Joshua A. Weiner (Molecular Neurobiology, 2021)

Characterisation and transferability of transcriptomic microsatellite markers for Nothofagus species - V. El Mujtar; M. López; S. Amalfi; F. Pomponio; S. Marcucci Poltri; S. Torales (New Zealand Journal of Botany, 2017)
Discriminant molecular markers are required for research on population genetics, as well as evolutionary studies involving identification of hybrids and parental species, or detection of the genome regions under selection. We provide a set of 27 transcriptomic microsatellite markers (SSRs) for South American Nothofagus species, derived from 73 Nothofagus alpina ( = N. nervosa) annotated unigenes. Rates of cross‐amplification ranged from 22% to 37%. Genetic characterisation of 22 transcriptomic SSRs for N. alpina and N. obliqua reveals low genetic variability, due to the general occurrence of one major allele at each locus, and high specificity, with few alleles shared between species (14%). At inter‐species level 95% of loci were discriminant, with a total G''st over loci of 0.9, indicating that alleles were mostly fixed for all loci in both species. At intra‐species level the number of markers with significant differentiation was 2.5 times higher for N. obliqua than for N. alpina populations. Moreover, transcriptomic SSRs showed higher performance compared with published anonymous microsatellites isolated from genome sequences without annotation. This set of transcriptomic microsatellites will be useful to the scientific community working on conservation and evolutionary aspects of Nothofagus species.

Distribution map of Ambrosia artemisiifolia L. (Asteraceae) in Italy - R. Gentili; F. Gilardelli; E. Bona; F. Prosser; A. Selvaggi; A. Alessandrini; F. Martini; P. L. Nimis; T. Wilhalm; M. Adorni; N. M. G. Ardenghi; E. Barni; et al. (Plant Biosystems, 2017)

Seroepidemiology of HEV and HAV in two populations with different socio-economic levels and hygienic/sanitary conditions - M. Zuin; C. Caserta; L. Romanò; A. Mele; A. Zanetti; R. Cannatelli; A. Giorgini; C. Tagliacarne; A. Amante; F. Marcucci; P. M. Battezzati (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Preclinical Pharmacokinetics Study of R- and S-Enantiomers of the Histone Deacetylase Inhibitor, AR-42 (NSC 731438), in Rodents - Hao Cheng; Zhiliang Xie; William P. Jones; Xiaohui Tracey Wei; Zhongfa Liu; Dasheng Wang; Samuel K. Kulp; Jiang Wang; Christopher C. Coss; Ching-Shih Chen; Guido Marcucci; Ramiro Garzon; et al. (The AAPS Journal, 2016)

How climate metrics affect global mitigation strategies and costs: a multi-model study - Mathijs J. H. M. Harmsen; Maarten van den Berg; Volker Krey; Gunnar Luderer; Adriana Marcucci; Jessica Strefler; Detlef P. Van Vuuren (Climatic Change, 2016)

How well do integrated assessment models represent non-CO2 radiative forcing? - Mathijs J. H. M. Harmsen; Detlef P van Vuuren; Maarten van den Berg; Andries F Hof; Chris Hope; Volker Krey; Jean-Francois Lamarque; Adriana Marcucci; Drew T Shindell; Michiel Schaeffer (Climatic Change, 2015)

Inappropriate prescription of allopurinol and febuxostat and risk of adverse events in the elderly: results from the REPOSI registry - L. Pasina; A. L. Brucato; C. D. Djade; P. Di Corato; S. Ghidoni; M. Tettamanti; C. Franchi; F. Salerno; S. Corrao; A. Marengoni; M. Marcucci; P. M. Mannucci; et al. (European Journal of Clinical Pharmacology, 2014)

Benefits and Challenges of Linking Green Infrastructure and Highway Planning in the United States - Daniel J. Marcucci; Lauren M. Jordan (Environmental Management, 2013)

A Case for Coastal Theory with Lessons from Planning Theory - Daniel J. Marcucci; James D. Brinkley; Lauren M. Jordan (Coastal Management, 2012)

Characterization of Silvestrol Pharmacokinetics in Mice Using Liquid Chromatography–Tandem Mass Spectrometry - U. V. R. Vijaya Saradhi; Sneha V. Gupta; Ming Chiu; Jiang Wang; Yonghua Ling; Zhongfa Liu; David J. Newman; Joseph M. Covey; A. Douglas Kinghorn; Guido Marcucci; David M. Lucas; Michael R. Grever; et al. (The AAPS Journal, 2011)

The contribution of seismic data in microzonation studies for downtown L’Aquila - G. Milana; R. M. Azzara; E. Bertrand; P. Bordoni; F. Cara; R. Cogliano; G. Cultrera; G. Di Giulio; A.M. Duval; A. Fodarella; S. Marcucci; S. Pucillo; et al. (Bulletin of Earthquake Engineering, 2011)

A Novel Ultrasensitive Hybridization-Based ELISA Method for 2-Methoxyphosphorothiolate MicroRNAs and Its In vitro and In vivo Application - Kenneth K. Chan; Zhongfa Liu; Zhiliang Xie; Ming Chiu; Hongyan Wang; Ping Chen; Sarah Dunkerson; Michael Chiu; Shujun Liu; Georgia Triantafillou; Ramiro Garzon; Carlo M. Croce; et al. (The AAPS Journal, 2010)

A morphological, caryological and morphometrical analysis of Teucrium euganeum Vis. and its allies - N Tornadore; R Marcucci; A Castagna; M Villani (Plant Biosystems, 2004)

The 1997 Umbria-Marche (Italy) earthquake sequence: analysis of the data recorded by the local and temporary networks - M. Cattaneo; P. Augliera; G. De Luca; A. Gorini; A. Govoni; S. Marcucci; A. Michelini; G. Monachesi; D. Spallarossa; L. Trojani; Xgums (Journal of Seismology, 2000)